Extracorporeal shock wave therapy as a treatment for heterotopic ossification. (1st August 2013) - Reznik, Jacqueline E; Milanese, Steve; Golledge, Jonathon; Biros, Erik; Gordon, Susan; Galea, Mary P
<x xml:space="preserve">Abstract</x> Background: Extracorporeal shock wave therapy (ESWT) is an intervention treatment in musculoskeletal conditions. Heterotopic ossification (HO) is a painful osseous condition of various origins, with the potential to cause significant incapacity. Objectives: To summarize the published data and assess the effectiveness of ESWT as a therapeutic intervention for patients with HO. Methods: A systematic search of the literature using Medline via Ovid, Scopus, CINAHL, and Web of Science databases. Reference lists of all articles found were also hand-searched. Articles were assessed using the Oxford Centre for Evidence Based Medicine (OCEBM) hierarchy of evidence and were critically appraised using the McMaster Critical Review Form for Quantitative Studies. A meta-analysis of data from four independent case studies totaling 52 HO patients treated with ESWT was performed. Outcome was assessed by pain and range of motion (ROM) of hip and knee flexion, since this was the only recorded movement data in the studies. Data were analyzed with a fixed effects model. Results: Only four articles met the inclusion criteria. Hierarchical evidence scores were low, but the articles scored well on the critical appraisal tool. ESWT led to an improvement in knee flexion by approximately 82% [95% confidence interval (CI): 66·58-96·87; P<0·001] and hip flexion of ∼10% (95% CI: 1·36-20·44; P = 0·086). Approximately 25% of relative improvement in ROM can be attributed to alleviation of pain after ESWT (r2 = 0·25; P = 0·496). Conclusion: ESWT may be associated with clinically significant improvement of ROM of lower extremities in patients with HO although larger studies are needed to confirm these findings.